Comprehensive Review of Healthcare Innovations in Enhancing Patient Outcomes through Advanced Pharmacy Practices - Olakunle Saheed Soyege; Collins Nwannebuike Nwokedi; Busayo Olamide Tomoh; shiata Yetunde Mustapha; Akachukwu Obianuju Mbata; Obe Destiny Balogun; Adelaide Yeboah Forkuo (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
The healthcare landscape is witnessing a transformative shift driven by advancements in pharmacy practices, as pharmacists increasingly play pivotal roles in patient care. This comprehensive review explores the impact of advanced pharmacy practices on enhancing patient outcomes. From evolving medication therapy management (MTM) programs to collaborative drug therapy management (CDTM) initiatives, the framework of advanced pharmacy practices is examined. The integration of pharmacogenomics, technological innovations, and patient-centric pharmacy models further contributes to the evolving landscape. Technological innovations, including telepharmacy services and the incorporation of automation and robotics, are reshaping the delivery of pharmaceutical care. The review delves into the integration of electronic health records (EHR) and explores challenges surrounding interoperability. Patient-centric models focus on education, community engagement, and specialized clinics for chronic care management, illustrating the potential of pharmacists in improving health literacy and overall patient wellness. Challenges such as regulatory considerations, the need for advanced training, and technological hurdles are discussed. Future directions highlight the imperative for ongoing education, regulatory adaptations, and technological advancements. Case studies and success stories showcase exemplary institutions and programs, providing insights into best practices. This review underscores the transformative power of advanced pharmacy practices in healthcare. It calls for continued research, regulatory support, and collaborative efforts to fully harness the potential of pharmacists in enhancing patient outcomes and contributing to the broader goals of healthcare improvement.